Effect of nitrogen-sulfur ratio on the digestibility of roughage based diet incubated with rumen liquor of buffalo - H. Fazaeli; M.R. Mashayekhi; H. Mansouri (Italian Journal of Animal Science, 2010)
In a compeletely randomized experiment, with factorial arrangment, the effects of three levels of urea and four levels of sulfur were tested on in vitro digestibilty and fermentability of rouphage based ration, incubated in rumen liqure of buffalo. Results showed that in vitro digestibility were not affected by the levels of urea, sulfur, or interaction of these factores. There was no variation among the treatments up to 12h of incubation for the cummulative gas production, but it was reduced when surful level increased from 0.37 to 0.41 or 0.45 percent of diet. Regardless of sulfur, urea significantly (p<0.05) affected gas production. There was also an interaction effect between nitrogen and sulfur levels on gas production, after 12 or 24h of fermentation (p<0.05) but not for the longer times of incubation. It could be concluded that 0.33% sulfur and 0.5 or 1.0% urea which provided a total N/S ratio of 4.68 to 5.28 or urea N/S ratio of 0.66 to 1.34 may be optimum ranges for rumen fermentations of rouphage based diets in buffalo.